Evaluation of serum Vitamin D3 level and its association with the severity of asthma and asthma control among the adult Indian population with bronchial asthma: A cross-sectional study - Dhwani Patel; Parul Vadgama; Shweta Patel; Vatsal Desai (Indian Journal of Allergy Asthma and Immunology, 2025)
BACKGROUND: Bronchial Asthma is one of the most common ailments prevalent in the Indian Population. Recent studies have suggested that Vitamin D3 may play a role in modulating immune responses and influencing asthma severity and control. However, the relationship between serum Vitamin D3 levels and asthma severity remains unclear, especially in the Indian population. OBJECTIVE: This study aimed to evaluate the serum Vitamin D3 levels in adults with bronchial asthma and assess its association with the severity of asthma and asthma control. MATERIALS AND METHODS: A cross-sectional study was conducted at the department of respiratory medicine of tertiary care center in western India. Serum Vitamin D3 levels were measured, and asthma severity was categorized using the National Asthma Education and Prevention Program (NAEPP) guidelines; asthma control was assessed using Global Initiative for Asthma (GINA) guidelines. The data were analyzed for correlations between serum Vitamin D3 levels, asthma severity, and asthma control. RESULTS: The study was conducted among eligible 45 patients with bronchial asthma. A significant inverse correlation was observed between serum Vitamin D3 levels and asthma severity (P < 0.05), with lower levels being associated with higher severity. In addition, lower Vitamin D3 levels were significantly correlated with poor asthma control (P < 0.05). CONCLUSION: Our findings suggest that lower serum Vitamin D3 levels are associated with greater asthma severity and poor asthma control in adults with bronchial asthma. Further longitudinal and interventional studies are needed to establish causality and the therapeutic benefits of Vitamin D3 in asthma management.